Mechanisms underlying the shape effect on nano-piezoelectricity. (November 2018) - Wang, R.J.; Wang, C.Y.; Feng, Y.T.; Tang, C.
Abstract: Piezoelectric nanowires (NWs) or nanotubes (NTs) are a vital component in nano-electromechanical and piezo-electronic device development. With various cross-sectional geometries achievable, the piezoelectric property-cross sectional shape relation is of fundamental interest. As existing studies (primarily based on first-principles calculations) are limited to ultrathin NWs or analysis based on continuum theories, the present work employs molecular statics (MS) simulation, which enables the examination of NWs/NTs up to cross-sectional size of 20.6 nm and elucidation of the underlying mechanisms at the atomic level. Analyses are carried out for NWs/NTs with experimentally observed geometry by comparing their size-dependence of effective piezoelectric constant and the radial distribution of the average dipole moment change with strain. The fraction of strain-sensitive dipoles, initial volume contraction and surface piezoelectricity were shown to control the shape effect on the piezoelectricity of ZnO nanostructures. Graphical abstract: fx1 Highlights: Atomistic study of shape effect on piezoelectricity of ZnO nanostructures. Shape effect on piezoelectricity arises from surface effects and interior structure. Strain-sensitive dipoles found to be the origin of interior structure effect. The greatest piezoelectric effect achieved for h-NTs at the size smaller than 7 nm.